2013
DOI: 10.1371/journal.pone.0051622
|View full text |Cite
|
Sign up to set email alerts
|

Union Makes Strength: A Worldwide Collaborative Genetic and Clinical Study to Provide a Comprehensive Survey of RD3 Mutations and Delineate the Associated Phenotype

Abstract: Leber congenital amaurosis (LCA) is the earliest and most severe retinal degeneration (RD), and the most common cause of incurable blindness diagnosed in children. It is occasionally the presenting symptom of multisystemic ciliopathies which diagnosis will require a specific care of patients. Nineteen LCA genes are currently identified and three of them account for both non-syndromic and syndromic forms of the disease. RD3 (LCA12) was implicated as a LCA gene based on the identification of homozygous truncatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 45 publications
0
21
2
Order By: Relevance
“…The same authors further showed that RD3 loss in a mouse model correlates with an aggressive neuroblastoma cancer. These findings are, however, in disagreement with a previous study showing that inactivation of both RD3 alleles in LCA12 patients does not correlate with extraocular symptoms ( Perrault et al, 2013 ). Recently, RD3 immunoreactivity was detected in normal human cell types, in particular in epithelial cells ( Aravindan et al, 2017 ).…”
Section: Introductioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The same authors further showed that RD3 loss in a mouse model correlates with an aggressive neuroblastoma cancer. These findings are, however, in disagreement with a previous study showing that inactivation of both RD3 alleles in LCA12 patients does not correlate with extraocular symptoms ( Perrault et al, 2013 ). Recently, RD3 immunoreactivity was detected in normal human cell types, in particular in epithelial cells ( Aravindan et al, 2017 ).…”
Section: Introductioncontrasting
confidence: 99%
“…Mutations in RD3 of human patients correlate with the phenotypical characteristics of LCA12. Genetic screening approaches in worldwide collaborative efforts uncovered deletion and missense mutations in rd3 , which were predicted to result in complete loss of function ( Friedman et al, 2006 ; Perrault et al, 2013 ). Immunoprecipitation showed that RD3 binds to photoreceptor specific guanylate cyclases GC-E and GC-F and both proteins are not detectable in rods and cones of RD3 deficient mice ( Azadi et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…RD3 has been extensively studied in the context of eye degeneration. It has been shown that truncation mutations in this gene are responsible for photoreceptor degeneration and inflict early onset of vision loss in patients with Leber Congenital amaurosis 12 [ 16 , 19 , 23 – 25 ]. Although RD3 has been shown to be associated with the leukemia gene product PML [ 17 ], the crucial role of RD3 in cancer biology has been overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…This condition prevents targeting of GC1 and leads to LCA1. Perrault et al (40) evaluated RD3 mutation in patients with LCA or early-onset severe retinal degeneration and identified three Rd3 mutations as follows: c.112C.T, c.136G.T, and a 2-bp deletion in c.137-138. The LCA12 phenotype strongly resembles LCA1.…”
Section: Lca1 Mutants Cannot Bind To Rd3-mentioning
confidence: 99%